The Beginning of Writing Culture among Steppe Nomads - Moldabay Т. (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2024)
In our study, we focus on periods leading up to the ancient Turkic Bitig script of the steppe nomads, analyzing the prerequisites and possibilities of writing culture. There are many petroglyphs and symbols that belong to early pictographic writing in the regions inhabited by steppe nomads. We have worked with these petroglyphs and symbols during several expeditions, including Shiveet Khairkhan, Arshan Khad, Hoyt-Tsenher, Baga-Uygur in Mongolia, Bichikt-Bom, Karakol in the Altai Mountains of Russia, Bizhik-Khaya, Bii-Khem in Tuva region, Karasuk inscriptions in the Khakassia, and AkBauyr, Zhetysu, Tangbaly, Terekti petroglyphs in Kazakhstan. Regarding the Greek data related to the period of object-based writing pertaining to the Saks, representatives of the steppe nomads, are presented. Focusing on the concepts formed from the writing history passed down through generation, this article considers its utilization among nomadic communities. It is clear that the tradition of counting the years and remembering well-known events, such as, “The Famine of the Year of the rabbit”, “The massacre of the Year of the Monkey” in nomadic culture, also the object-based writing and pictographic writing created the prerequisites of ancient Turkic script. This cultural-cognitive continuity is probably one of the main reasons why many petroglyphs and symbols are similar to the ancient Turkic script. Through this article, we have confirmed that all samples of historical writing periods are found in regions inhabited by steppe nomads. We aim to convey, their significant role in the formation of the ancient Turkic script and also their place in the world writing culture.